The potential of using biotechnology to improve cassava: a review - Chavarriaga Aguirre, Paul; Brand, Alejandro; Medina, Adriana; Prías, Mónica; Escobar Pérez, Roosevelt H.; Martínez, Juan; Díaz, Paula; López Carrascal, Camilo Ernesto; Roca, W.; Tohme, Joseph M. (Springer, 2016)
The importance of cassava as the fourth largest source of calories in the world requires that contributions of biotechnology to improving this crop, advances and current challenges, be periodically reviewed. Plant biotechnology offers a wide range of opportunities that can help cassava become a better crop for a constantly changing world. We therefore review the state of knowledge on the current use of biotechnology applied to cassava cultivars and its implications for breeding the crop into the future. The history of the development of the first transgenic cassava plant serves as the basis to explore molecular aspects of somatic embryogenesis and friable embryogenic callus production. We analyze complex plant-pathogen interactions to profit from such knowledge to help cassava fight bacterial diseases and look at candidate genes possibly involved in resistance to viruses and whiteflies—the two most important traits of cassava. The review also covers the analyses of main achievements in transgenic-mediated nutritional improvement and mass production of healthy plants by tissue culture and synthetic seeds. Finally, the perspectives of using genome editing and the challenges associated to climate change for further improving the crop are discussed. During the last 30 yr, great advances have been made in cassava using biotechnology, but they need to scale out of the proof of concept to the fields of cassava growers.